Analisis Potensi Pemanfaatan Air Hujan dan Perancangan Sistem Pemanenan Air Hujan (SPAH) pada Gedung Rektorat Universitas Andalas - Fadil Ikhsan Anugrah; Ansiha Nur; Puti Sri Komala; Wildani S. Sihombing; Syawal Andika P. (Universitas Andalas, 2024)
This research aims to analyze the potential of utilizing rainwater at the Rectorate Building of Universitas Andalas by examining both its quantity and quality, and by proposing an appropriate rainwater harvesting system (RWHS) design. The quantitative assessment employed 20 years (2003–2022) of maximum daily rainfall data collected from the Batu Busuak Station as the primary reference, supported by three additional stations. Based on a planned roof catchment area of 53.25 m², the calculated runoff discharge is 0.00013 m³/s, indicating that rainwater has considerable potential to serve as an alternative water source. The quality of rainwater shows that parameters such as temperature, dissolved oxygen (DO), chemical oxygen demand (COD), biochemical oxygen demand (BOD), turbidity, iron (Fe), and manganese (Mn) comply with the water quality standards set by the Regulation of the Minister of Health No. 2 of 2023 and Government Regulation No. 22 of 2021. However, the rainwater exhibits an acidic pH (4.14 ± 0.53) and elevated Escherichia coli levels (34.03 ± 41.86 MPN/100 mL), which exceed permissible limits and require treatment prior to use. The selection of suitable treatment technologies was conducted using the Simple Additive Weighting (SAW) method. The analysis showed that sand–calcite filtration system combined with chlorination as the most effective option, achieving a score of 95.90. This system is recommended for non-potable applications, specifically for toilet flushing, with an estimated water demand of 4.93 m³ and a ground tank capacity of 5 m³. The total estimated cost of the proposed RWHS is approximately IDR 26,258,000. Keyword: rainwater, rainwater quality, Log Pearson Type III, Simple Additive Weighting, Rainwater Harvesting System